An evaluation of formative assessment techniques employed at higher education institutions in Zimbabwe during the Covid-19 pandemic. - Watyoka Noreen; Gumbo Lilian; Chinyamunjiko Newton; Nyakurimwa Chalton Nyashadzenyu; Masukume Hebert (Global Scientific Journals, 2023)
The study focused on evaluating the effectiveness of formative assessments at Higher Education Institutions in Zimbabwe during the covid-19 pandemic. A case study research design was employed, where one department at Midlands State University was selected for analysis. The research adopted a qualitative research approach where interviews and focus group discussions were conducted to collect primary data. The study sample included 120 final-year undergraduate students and 11 lecturers in the department of Risk and Insurance. Thematic analysis of qualitative data revealed that the most common formative assessment methods that were used during the covid-19 pandemic were online quizzes, group work/presentations; work-related learning technology enhanced assessments, in-class tests, and lastly dissertations. The study established that group work, in-class tests, and online quizzes were the most effective formative assessment techniques employed during the covid-19 pandemic. However, lack of technological resources, delay in providing assessment feedback, and students' attitudes were the major challenges that affected the effectiveness of the formative assessment. The study recommends the training of lecturers and the use of informal methods of assessments.